Analysis of Program Implementation Health Business School (Uks) in Primary and Sub-Urban Urban in The District Jepara - lathifah, Ummu; Woro K H, Oktia; Yuniastuti, Ari (Universitas Negeri Semarang, 2019)
School health program is all the efforts made to improve the health of school age children at each track, the type and level of education. 2015 3863369 elementary school students and primary coverage of 92.23%. Networking health in elementary school students in Jepara in 2015 amounted to 98.15% in 2016 while the decline was 80%, while the national target of 100%, so the impact on the increase in morbidity in primary school students, demonstrated by the case of diarrhea (related to PHBs) in 2015 amounted to 67.7% of cases and increased in 2016 by 68% of cases, dengue morbidity rate 58.8% while the national target of 51%. This study aimed to analyze Implementation Program School Health Unit (UKS) at the primary school of Urban and Sub-Urban Jepara. The research method is qualitative. The focus of this study contains basic qualitative assessment of the implementation of the program the school health program, which includes standard and policy targets viewed from: aspects of input (human resources, funding, infrastructure, and SOPs), process (planning, implementation, monitoring and evaluation) and Output (UKS Service Improvement). Aspects of research results to implement UKS input already available and functioning properly. Both in terms of human resources, finance, infrastructure, and the unavailability of SOP: Human resources at the School of urban and school sub-urban enough, finance Educational urban and suburban use BOS funds, means school,Ã‚Â urban and sub-urban available are still lacking, SOP on urban and sub-urban schools are not available. Implementation aspects are aspects of planning for urban and suburban schools conducted annually by the joint meeting. Output Aspect Monitoring is done directly by the principal, recording and reporting do if someone is sick and referred. This research is expected to provide input in making the program refers to the government's program in the development of UKS program that objective can be achieved optimally, training UKS penaggung jawab specifically for teachers and complete record keeping and administration UKS.Ã‚Â